Georgia Demographic Change : Implications for Social Programs and Poverty - World Bank (Washington, DC, 2014)
This note provides an overview of demographic changes and their policy implications in Georgia, with particular reference to the poor. Georgia's population is expected to decline between 2010 and 2050, and this trend will be accompanied by a growing elderly cohort and a rising total dependency ratio. The note emphasizes four interrelated policy topics. These are labor force participation, labor force productivity, and potential cost pressures arising from the pension system and from the health sector. In each area, special attention is given to the linkages between these issues, social spending programs, and opportunities for targeting the poor. The note does not present specific policy recommendations, but instead outlines broad areas where future analytical work might be undertaken to arrive at more precise policy options. The note is structured as follows. The next section summarizes the key demographic trends underway in Georgia. Section three presents a profile of poverty and social spending by age. Section four analyzes the four policy issues listed in column two of table one. In each of these sections, the poverty reduction angle is emphasized. The final section provides a summary of the key messages, with an emphasis on policy priorities going forward.